ПЕРСПЕКТИВЫ РАЗВИТИЯ ИННОВАЦИЙ В РАМКАХ ОСВОЕНИЯ НЕФТЕГАЗОВЫХ МЕСТОРОЖДЕНИЙ АРКТИЧЕСКОГО РЕГИОНА - ТРЕТЬЯКОВ Н.А. ЧЕРЕПОВИЦЫН А.Е. (Zenodo, 2021)
The article discusses the prospects for the development of innovations in the development of oil and gas fields in the Arctic region. The article substantiates the need for predictive research in the field of oil and gas projects, which allows us to understand the possibilities of using digital technolo-gies in oil and gas projects in the Arctic. An assessment of the potential of oil and gas production in the implementation of projects aimed at developing the mineral resource base of the Arctic is given. Based on the analysis, a list of the most relevant areas of technological development in the field of dig-ital technologies that can increase the profitability of the development of deposits located in difficult natural and climatic conditions was formed.